Klippel Trenaunay Syndrome: A Case Report in an Adolescent Nigerian Boy - Ikpeme, Anthonia Asanye (Open Access Maced J Med Sci, 2015)
AIM: This is to report a case of Klippel Trenauay Weber syndrome in a fifteen year old Nigerian boy. This is a rare syndrome and it is the first case to be reported in UCTH Calabar. CASE PRESENTATION: Product of a full term uneventful pregnancy, delivered to non-consanguineous apparently healthy parents. At birth was noted to gradually develop swelling on the right leg, worse at the right foot. There was crossed hemi-hypertrophy with right leg bigger than the left. As child grew symptoms worsened, parents separated and eventually he was abandoned to the streets. He presented at University of Calabar Teaching Hospital for medical care at the age of fifteen years with lymphatic obstruction, persistent foul smelling drainage, lipodermatosclerosis of right foot as well psycho-social and financial constraints. The diagnosis was made with x-rays and Doppler studies of the lower limb vessels. He is currently being managed conservatively with compression dressings on the affected limbs, Antibiotics for the infection and analgesics. De-bulking surgery is being anticipated at this time. CONCLUSION: This is a case of KTWS presenting in adolescence and due to its rarity in Nigeria, this report is to increase awareness.